PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING (PBL) MATERI KEANEKARAGAMAN HAYATI PADA FASE E SMA/MA - Rahmi Lailatul Sakina; Nurhadi; Liza Yulia Sari (STKIP Subang, 2025)
E-modules are known as digital teaching materials that can be used anytime and anywhere through electronic devices such as laptops or smartphones. At SMAN 2 Sungai Tarab, Tanah Datar Regency, biology teaching materials that can be used by Phase E students that are in line with the curriculum used, namely the Independent Curriculum, are not yet available in the school library. During the biology learning process, the material is only sourced from teachers without being supported by teaching materials. The use of smartphones during biology learning has not been optimally utilized, and during the biology learning process, teachers have never used electronic modules. The purpose of this research is to provide a result in the form of an e-module on biodiversity based on Problem Based Learning that is valid and practical for senior high schools (SMA/MA). This development research uses a 4D model, which includes four processes: define, design, develop, and disseminate. This research has reached the develop stage which involves testing validity and practicality. At the define stage, front-end analysis, analysis of students, and task analysis were conducted. At the design stage, a PBL-based e-module was designed. In the development stage, data validity testing was carried out through questionnaires given to two lecturers and one biology teacher, and practicality testing through distributing questionnaires to biology teachers and students in phase E. The collected data were analyzed by percentage and processed descriptively. The results of the e-module validity test were 90.74% (very valid), the teacher practicality test was 96.67% (very practical), and the student practicality test was 89.90% (very practical). Based on the related findings, it can be concluded that the e-module that has been made for biodiversity material based on Problem Based Learning is very valid and very practical.